Bioactivity and chemical investigations of Pereskia Bleo and Pereskia Grandifollia / Sim Kae Shin - Sim, Kae Shin (2010)
Ethnopharmacological data has been one of the common useful criteria in drug discovery. Pereskia bleo and Pereskia grandifolia (Cactaceae), commonly known as ‘Jarum Tujuh Bilah’ in Malay and ‘Cak Sing Cam’ in Chinese have long been used as natural remedies in Malaysia. The experimental approach in the present study was based on bioassay-guided fractionation. The crude methanol and fractionated extracts of both Pereskia spp. were initially investigated for their biological activities such as antioxidant, antimicrobial and cytotoxic effect against five human cancer cell lines, namely nasopharyngeal epidermoid carcinoma cell line (KB), cervical carcinoma cell line (CasKi), colon carcinoma cell line (HCT 116), hormone-dependent breast carcinoma cell line (MCF7), lung carcinoma cell line (A549) and the non-cancer human fibroblast cell line (MRC-5) using in vitro cytotoxicity assay, in order to identify the bioactive extracts of both Pereskia spp.The hexane and ethyl acetate extracts of both Pereskia spp. generally showed stronger antioxidant activities than the other extracts. Ethyl acetate extracts of both Pereskia spp. also showed some mild antimicrobial activities against the tested bacteria.In the cytotoxicity assay, both Pereskia spp. exerted no damage to MRC-5 normal cells.The ethyl acetate extracts of both Pereskia spp. in general gave higher inhibition and stimulation values against various cancerous cell lines compared to other extracts. The cell deaths of the selected cancer cells elicited by the cytotoxic active extracts of both Pereskia spp. were found to be apoptotic in nature based on a clear indication of DNA fragmentation, which is a hallmark of apoptosis. In addition, the LUX RT-qPCR [realiii time reverse transcriptase–polymerase chain reaction (RT-qPCR) using LUX (Light Upon eXtension) primers] analysis showed that apoptosis elicited by the cytotoxic extracts on selected cancer cells was mediated by p53, caspase-3 and c-myc activation in different expression levels. Methyl palmitate, methyl linoleate, methyl α-linolenate and phytol were identified from the hexane extract of Pereskia bleo by GCMS analysis whilst methyl palmitate, methyl linoleate, methyl α-linolenate and methyl stearate were identified from the hexane extract of Pereskia grandifolia. From the results of the biological screenings, it is observed that the ethyl acetate extracts generally have stronger biological activities than other extracts. Further chemical investigations were thus directed to the ethyl acetate extracts of both Pereskia spp.2,4-Di-tert-butylphenol (1), α-tocopherol (2), phytol (3), ß-sitosterol (4),dihydroactinidiolide (5) and a mixture of sterols containing campesterol (6), stigmasterol (7) and β-sitosterol (4) were isolated from Pereskia bleo whilst 2,4-di-tertbutylphenol (1), α-tocopherol (2), ß-sitosterol (4) and mixture containing methyl palmitate (9), methyl oleate (10), methyl stearate (11) and 2,4-di-tert-butylphenol (1) were isolated from Pereskia grandifolia. It is interesting to note that 2,4-ditertbutylphenol(1), α-tocopherol (2) and ß-sitosterol (4) were isolated from the ethyl acetate extracts of both Pereskia spp. The cytotoxic activities of the isolated constituents were evaluated against the above human cell lines and further studies on their mode of action suggested that these activities are connected with induction of apoptosis.In addition, the toxicity of both Pereskia spp. was evaluated in vivo and were considered safe in acute oral toxicities in experimental mice. The screening of the locally grown Pereskia bleo and Pereskia grandifolia indicated the presence ofalkaloids, but the concentration was very low. The findings of Pereskia bleo and Pereskia grandifolia in the present study provided scientific validation on the use of the leaves of both Pereskia spp. for the treatment of cancer. Further studies on the mutagenic and toxicity effect over a longer period of time involving detection of effects on vital organ functions should be carried out to ensure that the plants are safe for human consumption.